2018
DOI: 10.21082/bp.v19n2.2018.79-88
|View full text |Cite
|
Sign up to set email alerts
|

Uji Mutu dan Keefektifan Metarhizium anisopliae Isolat Kalimantan Tengah Terhadap Oryctes rhinoceros (Coleoptera: Scarabaeidae) [Quality Test and Effectiveness of Metarhizium anisopliae Isolates From Central Kalimantan Against Oryctes rhinocerus]

Abstract: ABSTRAKHama Oryctes rhinoceros (Coleoptera: Scarabaeidae) merupakan hama penting tanaman kelapa . Pengendalian O. rhinoceros dapat dilakukan dengan berbagai cara yaitu secara fisik, mekanik, hayati, dan kimiawi. Cendawan Metarhizium anisopliae merupakan agens hayati yang dapat menekan perkembangan hama O. rhinoceros. Efektivitas cendawan M. anisopliae sangat ditentukan oleh kualitas/mutu konidia cendawan tersebut yang meliputi kerapatan, viabilitas dan patogenitasnya terhadap hama sasaran. Untuk itu telah dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Coconut shoot borer pests have been known as pests that attack coconut or oil palm plants with a reduced population of coconut plants on the island of Java there is a tendency to move habitat from coconuts in plants other than coconut including agave or which is still one genus with coconut. (Siswanto & Trisawa, 2018) reported that coconut shoot borer beetle pests also attack sago, sugarcane, and nenas plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coconut shoot borer pests have been known as pests that attack coconut or oil palm plants with a reduced population of coconut plants on the island of Java there is a tendency to move habitat from coconuts in plants other than coconut including agave or which is still one genus with coconut. (Siswanto & Trisawa, 2018) reported that coconut shoot borer beetle pests also attack sago, sugarcane, and nenas plants.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015 obtained ISSN: 2614-1558 | 90 information on the attack of coconut shoot borer pests (Oryctes rhinoceros L.) as it attacks on coconut and oil palm crops. According to (Siswanto & Trisawa, 2018) in addition to palms, betel nut, sago, pineapple and bananas, the Agave plant is one of the minor hosts of the coconut shoot borer pest.…”
Section: Introductionmentioning
confidence: 99%